Developing an Organizational Readiness Framework for BIM Implementation in Large Design Companies - Phung, Quan; Tong, Nguyet (International Journal of Sustainable Construction Engineering and Technology, 2021)
BIM is a set of interacting processes, human, information, and technology components. A successful BIM implementation in organizations requires not only the  consideration of technical issues but also other organizational changes. However, existing standards, guidelines, and protocols mainly focus on guiding practitioners the right way to develop and implement BIM technology. Change management for BIM implementation in organizations has not had sufficient attention in practice to other components, which would result in ineffectiveness and inefficiency. In the process of organizational change, readiness is considered a first critical step to break the status quo before going to the adoption and institutionalization phase when the necessary changes are implemented, and the system is internalized. This study aims to develop a comprehensive organizational readiness framework for BIM implementation to help large design firms build up organizational capabilities in the BIM adoption phase. Twelve semi-interviews were conducted with the participation of BIM specialists working in design companies, BIM consultants, and Design-Build contractors in Vietnam. The framework consists of six key elements: strategy, organizational structure, process, people, technology, and information management. Each of these elements was developed with specific criteria to support design companies to assess and create organizational readiness for BIM implementation. The paper ends with a further discussion on influential factors in creating organizational readiness for BIM.